From Bedside to Budget: ERACS Protocol in National Healthcare Insurance Era, Is it Still Relevant? - Ageng Sunjoyo; Muzakar Isa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Background: This systematic review aims to resolve the critical conflict between the clinically superior, cost-efficient Enhanced Recovery After Cesarean Section (ERACS) protocol and the financially restrictive BPJS/INA-CBGs national healthcare financing system in Indonesia. The objective is to synthesize evidence on ERACS's efficiency to inform policy recommendations that support its equitable and sustainable adoptionMethods: Following PRISMA guidelines, the methodology involved synthesizing 27 studies published between 2020-2025 across major databases (e.g., PubMed, Cochrane). Included studies were RCTs, cohort, or comparative observational designs focusing on Length of Stay (LOS), cost-related outcomes, pain control, and complication ratesResults: ERACS consistently demonstrated a significant reduction in patient Length of Stay, with reductions ranging from 4 to over 57 hours (e.g., 2.85 days vs. 5.25 days in one major study). The protocol was also associated with a significant decrease in hospital expenditures, including a reported reduction in median direct costs of approximately US$349 per cesarean delivery. Furthermore, ERACS consistently led to improved postoperative pain control, fewer complications, and higher maternal satisfactionConclusion: ERACS offers substantial clinical and economic benefits that align with the goals of Indonesia’s universal health coverage system. The existing evidence provides critical support for policy reforms that must align the fixed BPJS tariff structure with this proven clinical best practice to ensure its widespread, sustainable, and equitable adoption within the national healthcare system.